The ‘division of labour’ model of eye evolution - Arendt, Detlev; Hausen, Harald; Purschke, Günter (Philosophical transactions of the Royal Society of London. Series B, Biological sciences, 2009)
The ‘division of labour’ model of eye evolution is elaborated here. We propose that the evolution of complex, multicellular animal eyes started from a single, multi-functional cell type that existed in metazoan ancestors. This ancient cell type had at least three functions: light detection via a photoreceptive organelle, light shading by means of pigment granules and steering through locomotor cilia. Located around the circumference of swimming ciliated zooplankton larvae, these ancient cells were able to mediate phototaxis in the absence of a nervous system. This precursor then diversified, by cell-type functional segregation, into sister cell types that specialized in different subfunctions, evolving into separate photoreceptor cells, shading pigment cells (SPCs) or ciliated locomotor cells. Photoreceptor sensory cells and ciliated locomotor cells remained interconnected by newly evolving axons, giving rise to an early axonal circuit. In some evolutionary lines, residual functions prevailed in the specialized cell types that mirror the ancient multi-functionality, for instance, SPCs expressing an opsin as well as possessing rhabdomer-like microvilli, vestigial cilia and an axon. Functional segregation of cell types in eye evolution also explains the emergence of more elaborate photosensory-motor axonal circuits, with interneurons relaying the visual information.
Gesehen am 18.05.2017